The Impact of Islamic Financial Inclusion on Micro-Enterprises Capital: The Case of Sumedang Regency - Mohammad Iqbal Irfany; Nur Wulan; Resfa Fitri (IQTISHODUNA, 2022)
Financial inclusion is essential, especially for small and micro-enterprises who often experience issues accessing financial institutions. This inclusion aims to eliminate all financial barriers, including price and non-price, to public access to financial services to reduce societal inequality. This study aims to analyze the effect of Islamic financial inclusion on the capital growth of micro-enterprises in the Sumedang Regency. Employing descriptive analysis and SEM-PLS on primary data with 100 respondents from micro-enterprises who used financial services, the results show that respondents' average Islamic financial inclusion was 59 percent, above the national level. It also found that Islamic financial inclusion had a positive effect on the development of micro-enterprise capital, which indicates that people classified in the micro-business group have broad access to Islamic financial products and services might increase business capital. In addition, the influence of Islamic financial inclusion and mentoring variables on positive capital development means that any increase in the value of Islamic financial inclusion and mentoring will increase capital development.